ANDROID BASED ADVERTISING REMINDER SYSTEM - Putra, Toni Wijanarko Adi; Saputro, Alif Budi; Solechan, Achmad; Hartono, Budi (Jurusan Teknologi Informasi Universitas Semarang, 2023)
The aim of this research is to introduce an Android-based reminder system that automatically notifies Surya Media Advertising employees of expired leases. Android is a